ANALYSIS OF PRODUCTIVITY OF DIGGING TOOLS AND TRANSPORTATION EQUIPMENT IN STRIPING SOIL LAYERS USING THE SIMPLEX METHOD - Nilam Desiana Nurdin; Didit Welly Udjianto (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
One operation in mining coal is transfer layer cover (overburden). To increase capacity handling burden, necessary planning needs equipment, machine mechanical form tool load, And tools capable of transporting operate optimally depending on the situation And condition in the field. Demolition layer land cover (overburden) begins with excavation of the front and transportation to the disposal area with tool mechanical excavator PC 2000 with a capacity of 123 buckets and Komatsu HD 785 dump truck capacity of 603. Calculations use a tool calculated, the simplex minimization method And are processed using POM software. On study this obtained results with four iterations obtained results 7,728 and If compared to with manual calculations obtained 7.1 then tools needed. In 1 fleet there are 7 HD units for production can be fulfilled.